2008
DOI: 10.1063/1.2970033
|View full text |Cite
|
Sign up to set email alerts
|

Controllable resistance and temperature dependency of carbon nanotube bundles

Abstract: We report the controllable resistance of multiwalled carbon nanotube bundles for the possible application in nanoscale electronics. The resistance as well as the variation of resistance with temperature depends on the bundle diameter. The larger the diameter, smaller is the resistance and weaker is the variation of resistance with temperature that make the bundles advantageous in nanoscale electronics and in some other applications. As the resistance and the variation can be controlled by monitoring the bundle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
(45 reference statements)
2
15
0
Order By: Relevance
“…This is believed to be due to the Joule heating of NTs. 18,19 We have also investigated two more devices with two segments and found that high resistive segment breaks at a lower current. Raman spectra, taken prior to the breakdown experiments as shown in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…This is believed to be due to the Joule heating of NTs. 18,19 We have also investigated two more devices with two segments and found that high resistive segment breaks at a lower current. Raman spectra, taken prior to the breakdown experiments as shown in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…With the aforementioned mechanism of energy harvesting, the voltage induced by the nanofluidic flow can be estimated as V = RAsev, 15 where R is the CNT's resistance, s is the average charge carrier density, e is the electronic charge and is 1.6 Â 10 À19 C, A is the cross section area of the CNT, and v is the average drifting velocity of Cl À ions in the FSS. Based on previous experimental results, 38,39 the resistance, R, is related to the CNT geometry as R = 4R 0 L/(pD 2 ) where R 0 is the reference resistance of 400 O nm. 38 The temperature dependence of resistance is negligible (for the range of 300-360 K considered in this paper).…”
Section: Resultsmentioning
confidence: 99%
“…6(a). 15,16 The temperature distribution is almost uniform along the length of long metallic NTs as heat removal mainly takes place through the electrodes [ Fig. 6(a)].…”
Section: Fig 4 (A) I-t and (B) T-t Curves At 18 V (C) I-t And (D)mentioning
confidence: 99%
“…[17][18][19][20] NT arrays can be suitable for low resistance interconnects as the resistance decreases as the diameter of the arrays is increased. 15 Here, we have reported two-probe measured transport properties of millimeter long arrays of multiwalled NTs (MWNTs) in the view point of technological applications and fundamental understandings. The current increase rapidly with voltage before the breakdown occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation